Neural Stem Cell Transplantation Is Associated with Inhibition of Apoptosis, Bcl-xL Upregulation, and Recovery of Neurological Function in a Rat Model of Traumatic Brain Injury. Issue 7 (July 2017) - Pang, Ai-Lan; Xiong, Liu-Lin; Xia, Qing-Jie; Liu, Fen; Wang, You-Cui; Liu, Fei; Zhang, Piao; Meng, Bu-Liang; Tan, Sheng; Wang, Ting-Hua
Traumatic brain injury (TBI) is a common disease that usually causes severe neurological damage, and current treatment is far from satisfactory. The neuroprotective effects of neural stem cell (NSC) transplantation in the injured nervous system have largely been known, but the underlying mechanisms remain unclear, and their limited sources impede their clinical application. Here, we established a rat model of TBI by dropping a weight onto the cortical motor area of the brain and explored the effect of engrafted NSCs (passage 3, derived from the hippocampus of embryonic 12- to 14-d green fluorescent protein transgenic mice) on TBI rats. Moreover, RT-PCR and Western blotting were employed to investigate the possible mechanism associated with NSC grafts. We found rats with TBI exhibited a severe motor and equilibrium dysfunction, while NSC transplantation could partly improve the motor function and significantly reduce cell apoptosis and increase B-cell lymphoma–extra large (Bcl-xL) expression at 7 d postoperation. However, other genes including Bax, B-cell lymphoma 2, Fas ligand, and caspase3 did not exhibit significant differences in expression. Moreover, to test whether Bcl-xL could be used as a therapeutic target, herpes simplex virus (HSV) 1 carrying Bcl-xL recombinant was constructed and injected into the pericontusional cortices. Bcl-xL overexpression not only resulted in a significant improvement in neurological function but also inhibits cell apoptosis, as compared with the TBI rats, and exhibits the same effects as the administration of NSC. The present study therefore indicated that NSC transplantation could promote the recovery of TBI rats in a manner similar to that of Bcl-xL overexpression. Therefore, Bcl-xL overexpression, to some extent, could be considered as a useful strategy to replace NSC grafting in the treatment of TBI in future clinical practices.